Conventional Development: Between Economic Progress and Environmental Damage - Ahmad Mundir; Abdul Wadud Nafis; Nikmatul Masruroh (IJIEF: Indonesian Journal of Islamic Economics and Finance, 2025)
Economic development in Indonesia has experienced rapid growth in recent decades. However, conventional development models that focus on the exploitation of natural resources often neglect aspects of environmental sustainability. This study aims to examine conventional development patterns that have an impact on environmental degradation and evaluate the effectiveness of policies that have been implemented to reduce their negative impacts. The method used in this study is a literature study with a qualitative approach based on data analysis from scientific journals, research reports, and policy documents in the last five years. The results show that development based on industry and natural resource extraction has caused significant deforestation, pollution, and ecosystem damage. Although the government has adopted various environmental policies such as a moratorium on oil palm plantation permits and a reforestation program, the implementation of these policies still faces various challenges, especially in aspects of supervision and law enforcement. Therefore, a more comprehensive strategy is needed, including the integration of a green economy, environmental economic implementation instruments, and increased public awareness and participation in maintaining environmental sustainability. With the right steps, Indonesia can achieve a balance between economic growth and environmental conservation to achieve sustainable development.